The Strategic Role of Accounting Information Systems in Financial and Non-Financial Performance - Harahap, Eliya Fatma (Indonesian Scientific Publication, 2025)
This study provides a narrative review, highlighting its contribution to profitability, cost efficiency, sustainability, customer satisfaction, and innovation. The summary has been simplified to ensure readability and reduce technical density. Comparisons between developed and developing countries indicate varying magnitudes of impact, with transformative potential more evident in resource-constrained economies. The discussion further identifies systemic factors—including regulation, organizational culture, and digital infrastructure—as critical determinants of AIS effectiveness, while integration with enterprise resource planning, blockchain, and business intelligence technologies strengthens competitiveness. Despite these advances, limitations remain, particularly the underrepresentation of small and medium-sized enterprises in developing regions and the reliance on cross-sectional methodologies. Future research is recommended to explore longitudinal and context-sensitive analyses that incorporate human and behavioral dimensions. Overall, the findings emphasize that enhancing AIS quality and aligning adoption with digital transformation are essential strategies for sustaining organizational performance and competitiveness.